Septic Arthritis of the Pubic Symphysis in Adult: A Case Report - Labronici, Pedro José; Tavares, Augusto Khede; Silva, Luiz Henrique Penteado; Pires, Robinson Esteves Santos; Giordano, Vincenzo; Loures, Fabrício Bolpato (Revista Brasileira de Ortopedia, 2021)
Septic arthritis of the pubic symphysis is a rare condition. Risk factors include trauma, low-grade infection, urological or gynecological procedures, malignant tumors of the pelvis, sports, and intravenous drug abuse. This report describes a case of septic arthritis of the pubic symphysis in a 23-year-old male patient with no history of pelvic surgery, previous infections, or intense physical activity. Arthritis was diagnosed by blood culture positive for Enterococcus spp. and yeasts, and the patient was treated with antibiotics. This case emphasizes the importance of complementary exams to aid the treatment of septic arthritis of the pubic symphysis and shows that an invasive procedure, such as pubic symphysis puncture biopsy, may not be required.
Keywords: septic arthritis; osteitis; pubic symphysis